Pengaruh Likuiditas, Leverage, Struktur Modal Dan Profitabilitas Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2018-2021 - Helisa Putria Sosanto; Hottua Samosir; Heri Enjang Syahputra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this research is to determine the relative or simultaneous influence of liquidity, leverage, capital structure and profitability on dividend policy in manufacturing companies listed on the IDX between 2018 and 2021. In 2018–2021 there were 212 manufacturing companies.in the population. Thirty-two companies were included in the purposive sample obtained. Multiple linear regression analysis is the method used for data analysis. The research findings show that, in contrast to liquidity, leverage, capital structure, and profitability, which have no effect on dividend policy, profitability has a slightly favorable impact. Additionally, it is stated that profitability, capital structure, liquidity, and leverage all have a positive impact on dividend policy.